2011
DOI: 10.1523/jneurosci.2968-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

On the Dynamic Nature of the Engram: Evidence for Circuit-Level Reorganization of Object Memory Traces following Reactivation

Abstract: Research has implicated the perirhinal cortex (PRh) in several aspects of object recognition memory. The specific role of the hippocampus (HPC) remains controversial, but its involvement in object recognition may pertain to processing contextual information in relation to objects rather than object representation per se. Here we investigated the roles of the PRh and HPC in object memory reconsolidation using the spontaneous object recognition task for rats. Intra-PRh infusions of the protein synthesis inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 70 publications
4
46
0
Order By: Relevance
“…The intra-PRh result is consistent with numerous studies implicating PRh in object memory processing, including reconsolidation (Buckley 2005;Murray et al 2007;Winters et al 2008Winters et al , 2011Brown et al 2012;Balderas et al 2013). Furthermore, stimulating muscarinic receptors during memory reactivation with systemic or intra-PRh delivery of muscarinic receptor agonists mimicked the memory destabilizing effects of salient novelty; when strongly encoded or relatively remote memories were reactivated in the absence of the contextual change, they were not destabilized unless oxotremorine or carbachol was administered prior to the reactivation phase.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The intra-PRh result is consistent with numerous studies implicating PRh in object memory processing, including reconsolidation (Buckley 2005;Murray et al 2007;Winters et al 2008Winters et al , 2011Brown et al 2012;Balderas et al 2013). Furthermore, stimulating muscarinic receptors during memory reactivation with systemic or intra-PRh delivery of muscarinic receptor agonists mimicked the memory destabilizing effects of salient novelty; when strongly encoded or relatively remote memories were reactivated in the absence of the contextual change, they were not destabilized unless oxotremorine or carbachol was administered prior to the reactivation phase.…”
Section: Discussionsupporting
confidence: 86%
“…Rats also showed significant novel object preference in all conditions (all P , 0.01), except for saline/anisomycin (P ¼ 0.738). We have previously demonstrated that the intra-PRh blockade of object memory destabilization is reactivation-dependent (Winters et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P-values ,0.05 were accepted as statistical significance. The first minute of exploration was used for statistical analysis (reactivation and test phases), since it was reported that novel objects discrimination is more evident during that period of time (Dix and Aggleton 1999;Mumby et al 2002;Winters et al 2011).To test whether pharmacological inhibition of AMPA receptors disrupts retrieval of ORM we infused vehicle or CNQX 15 min before memory reactivation in the perirhinal cortex. Rats were exposed to two copies of the same object in the sample phase (Fig.…”
mentioning
confidence: 99%
“…Importantly, STM was unaffected by AP5. Experiments in which protein synthesis was inhibited by anisomycin infusion into the perirhinal cortex showed that this region is indispensable for the occurrence of ORM reconsolidation (Winters et al 2011). In another study, it was established that glutamate receptors in the perirhinal cortex play a role in ORM formation.…”
mentioning
confidence: 99%